Self-regard in the structure of personality behavioural manifestations - LEVUS, NADIA (Journal of Education Culture and Society, 2020)
The article focuses on the issue of self-regard connected with behavioural manifesta-tions of personality. By means of comparative, correlation and factorial analysis it is proven that positive self-regard is accompanied by a decreasing level of suicidal risk as well as by creativity growth. Self-acceptance, positive attitude towards oneself ensures a harmonious existence and a high level of personality self-identifi cation. Higher level of self-regard is revealed in younger age categories where it is based on optimistic life prospects and a creative approach to solving life problems. Creativity combined with self-liking becomes a certain ability that helps overcome crisis situations and facilitates removal of personal peculiarities connected with proneness to suicide. Among the creative skills and abilities foregrounded are creative approach, creative imagination and creative intuition.